Methods in chemical process safety. - Khan, Faisal I.; Abbassi, Rouzbeh (Academic Press, an imprint of Elsevier, 2018)
Methods in Chemical Process Safety, Volume Two, the latest release in a serial that publishes fully commissioned methods papers across the field of process safety, risk assessment, and management and loss prevention, aims to provide informative, visual and current content that appeals to both researchers and practitioners in process safety. This new release contains unique chapters on offshore safety, offshore platform safety, human factors in offshore operation, marine safety, safety during well drilling and operation, safety during processing (top side), safety during transportation of natural resources (offshore pipeline), and regulatory contextHelps acquaint the reader/researcher with the fundamentals of process safetyProvides the most recent advancements and contributions on the topic from a practical point-of-viewPresents users with the views/opinions of experts in each topicIncludes a selection of the author(s) of each chapter from among the leading researchers and/or practitioners for each given topic